Travel among Early Christians: A Socio-theological Analysis of Pauline and Ignatian Communities - Borges, Jason, (Biblical Interpretation Series ;, 2025)
Travel Among Early Christians approaches intercommunal movement between churches as a valuable source of insights regarding social and theological aspects of early Christianity. Incorporating theories from mobility studies and ancient institutions that facilitated travel, Borges traces how travel functioned as a formative practice among early Christians' group identities, and signified a new cosmic reality regarding their unity in Christ. Borges investigates six specific travel events in Pauline and Ignatian churches, noting how mobility became a distinctive and revealing aspect of early Christianity.